Volume 3B: General 1993
DOI: 10.1115/93-gt-337
|View full text |Cite
|
Sign up to set email alerts
|

A Design Procedure for Effervescent Atomizers

Abstract: A methodology for the design of effervescent atomizers is described. The objective is to achieve sprays of minimum mean drop size for any stipulated values of liquid flow rate, air supply pressure, and air/liquid ratio. Application of the method leads to optimum values for all the key atomizer dimensions, including the number and size of the air injection holes, and the diameters of the mixing chamber and discharge orifice. It also enables optimum dimensions to be determined for a convergent-divergent nozzle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…The initial and boundary conditions were defined according to previously published models. [16][17][18] The upstream flow regime and initial flow morphology parameters such as the liquid film and bubble size were determined through the visualization experiments. 19 The atomizer geometries (mixing chamber diameter, exit orifice diameter, exit orifice length) are same with the visualization experiments, as can be seen in Figure 2 (left).…”
Section: Solvability Conditions and Verificationmentioning
confidence: 99%
“…The initial and boundary conditions were defined according to previously published models. [16][17][18] The upstream flow regime and initial flow morphology parameters such as the liquid film and bubble size were determined through the visualization experiments. 19 The atomizer geometries (mixing chamber diameter, exit orifice diameter, exit orifice length) are same with the visualization experiments, as can be seen in Figure 2 (left).…”
Section: Solvability Conditions and Verificationmentioning
confidence: 99%
“…However, Kushari [5] showed that droplet size decreases with the increase of mixing chamber length. Both Ferreira et al's [6] and Kushari's [5] results showed that the ratio of the exit orifice area to the air injection area influences spray mean drop size in internal mixing twin-fluid atomizers, the same with effervescent atomizers [7]. Shafaee [8] et al found that, increasing of the mixing chamber length causes a little decrease in spray cone angle.…”
Section: Introductionmentioning
confidence: 98%
“…Because of the potential for high volume production, there has been interest in developing nozzle atomization SP, using modified atomization techniques to reduce droplet sizes. One such approach is twin‐fluid atomization (TFA‐SP), which involves the mixing of gas and liquid, to give smaller droplet sizes than conventional pressure sprays 1,8 . Zirconia powders with maximum sizes of only 1–3 μm, similar to what can be achieved by ultrasonic atomization, 9 have been reported from TFA‐SP 10 …”
Section: Introductionmentioning
confidence: 99%